Comment la téléconsultation médicale « en autonomie » infléchit-elle les rapports de pouvoir dans la relation médecin-patient ? - Cécilia Calheiros (Netcom)
Since the second half of the 20th century, the French healthcare system has undergone a series of changes (such as budgetary policy, the questioning of medical authority, increasing patient autonomy, etc.) which have notably resulted in altering the framework of the practice of medicine and the doctor-patient relationship. The massive use of teleconsultation since 2020 raises questions about the impact of putting the body at a distance and how it modifies the doctor-patient relationship by reconfiguring information asymmetries and by producing a context of increased "coerced" trust in the patient's word. This article analyzes a particular type of teleconsultation, namely those taking place in autonomy. By this expression we mean the ones that take place on private platforms between an autonomous patient, without a connected instrument at his disposal, and a private general physician.